1992
DOI: 10.1246/cl.1992.1357
|View full text |Cite
|
Sign up to set email alerts
|

Base-Induced Selective Ring Opening of 1-Arylbenzo[b]thiophenium Salts

Abstract: Reactions of 1-arylbenzo[b]thiophenium salts with methoxide anion in methanol caused the fission of the S+-C(2) bond of the thiophenium ring to produce o-(phenylthio)phenyl-substituted methoxyethenes, allenes, or alkynes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Because 1-alkyl-1-benzothiophenium salts are much higher in chemical reactivity than the corresponding 1-phenyl-1-benzothiophenium salts, the cycloadducts, 1-phenyl-2,3-dihydro-1-benzothiophenium salts, are expected to be more reactive. Previously, we reported that 1-aryl-1-benzothiophenium salts undergo the ring-opening reaction upon treatment with methoxide anion . To compare the reactivity of the cycloadducts with that of 1-phenyl-1-benzothiophenium salts, we examined the reaction of the cycloadducts with sodium methoxide in methanol.…”
Section: Resultsmentioning
confidence: 99%
“…Because 1-alkyl-1-benzothiophenium salts are much higher in chemical reactivity than the corresponding 1-phenyl-1-benzothiophenium salts, the cycloadducts, 1-phenyl-2,3-dihydro-1-benzothiophenium salts, are expected to be more reactive. Previously, we reported that 1-aryl-1-benzothiophenium salts undergo the ring-opening reaction upon treatment with methoxide anion . To compare the reactivity of the cycloadducts with that of 1-phenyl-1-benzothiophenium salts, we examined the reaction of the cycloadducts with sodium methoxide in methanol.…”
Section: Resultsmentioning
confidence: 99%